The synthesis and formation mechanism of nonpolar InN nanoplates. Issue 35 (20th August 2021) - Song, Wenqing; Li, Tao; Zhang, Lei; Zhu, Wenhui; Wang, Liancheng
Abstract : High-crystal-quality nonpolar indium nitride (InN) nanoplates were synthesized via deploying controllable chemical vapor deposition (CVD) technology using the M -plane of GaN nanowires (NWs) as a template. Abstract : High-crystal-quality nonpolar indium nitride (InN) nanoplates were synthesized via deploying controllable chemical vapor deposition (CVD) technology using the M -plane of GaN nanowires (NWs) as a template, with features creating a potential advantage for their use in terahertz emitter/detector devices. The formation of the 2D InN nanosheets may have been due to self-limiting epitaxial growth, which is in turn explained by lattice induction theory and surface distortion effects.